Misoprostol to induce birth number of cases in the 2003-2004 HNCH - Arévalo, Jorge (2015)
OBJETIVE: To determine labor, delivery and perinatal characteristics and outcomes of patients who were induced with intravaginal misoprostol. MATERIALS AND METHODS: A descriptive, retrospective study developed in the Department of Gynecology and Obstetrics Hospital Nacional Cayetano Heredia during the period July 2003 to June 2004. The medical records of 139 patients were evaluated, indicating end gestation and who had administered one dose of 25 micrograms of intravaginal misoprostol. RESULTS: 113 vaginal deliveries, of which 85 (61.2%) occurred before 24 hours was obtained, showing a shorter time in multiparous (17.4 ± 10.4 hours) versus gilts (21.1 ± 13.3 hours); 58 (41.7%) patients required only 1 dose of misoprostol to have a vaginal birth. Ceráreas rate was 18.7% (26 cases), the leading cause not reassuring pattern in 8 patients (30.8%). There were two cases of tachysystole (1.4%) and 1 hyperstimulation (0.7%) syndrome. 20% of births presented meconium. there was 1 (0.7%) case of Apgar <7 at 5 minutes. 4 infants (2.8%) were hospitalized. There were no maternal or neonatal death. CONCLUSIONS: The use of intravaginal misoprostol is useful for induction of labor. Low rates of maternal and perinatal adverse effects occurred.